Chronic Obstructive Pulmonary Disease and Stroke. (4th July 2018) - Corlateanu, Alexandru; Covantev, Serghei; Mathioudakis, Alexander G.; Botnaru, Victor; Cazzola, Mario; Siafakas, Nikolaos
ABSTRACT: Chronic obstructive pulmonary disease (COPD) is currently the fourth leading cause of death in the world and its incidence and prevalence is on the rise. It is evident that COPD is linked to cardiovascular disease. In the last years, several studies demonstrated that COPD may also be a risk factor for stroke, another major cause of death worldwide. Taking in consideration that COPD has multiple comorbidities it is hard to say whether COPD is an independent risk factor for stroke or it is due to confounding effect. This review is aimed to discuss current data on COPD and stroke, potential links, therapy, and prevention. Current data suggest that COPD may increase the risk of hemorrhagic stroke. The incidence of other stroke subtypes may also be increased in COPD or may be due to confounding effect. However, COPD patients who have stroke are at risk for pulmonary and extrapulmonary complications. We conclude that more studies are needed to further clarify the links between COPD and stroke. The management of COPD as well as the use of prevention therapy is essential to decrease the risk for stroke and should be at special attention in pulmonary medicine and neurology.